THE ROLE OF MUSEUM PEDAGOGY IN THE FORMATION OF A SENSE OF PATRIOTISM OF FUTURE TEACHERS IN THE NEW UZBEKISTAN - Xolmuminova Dilfuza (Web of Journals Publishing, 2024)
In this article, the positive value of museum pedagogy, the history of its origin, and the importance of educating future teachers in the spirit of patriotism, along with pedagogical technologies in the educational system, as a factor that determines the development of the society, the effectiveness of the educational system considered.
Keywords: museum, museology, exhibit, integration, museum pedagogy, virtual museum, virtual tour, renaissance.